Infrastructure procurement framework for local authority - Salleh, Dani; Ismail, Mazlan (Universiti Utara Malaysia Press, 2015)
The spread of infrastructure requirements and variety in mechanisms used to secure contributions (infrastructure provision) from private sector was a reflection of the institutional framework in planning system.The study has identified that although both private and local authorities have a good understanding of the fundamental of concept of local infrastructure provision and the arguments for and against the use of private provision, there are still considerable areas of uncertainty surrounding the precise definition (as prescribed in the relevant legislations) and measurements of the key elements pertaining to local infrastructure.The findings revealed that the previous studies has tended to examine the nature of the practice of the infrastructure delivery within the framework of national economy and very little focus has been given to a comprehensive examination on how private developers can be involved in local infrastructure development.The primary problem is that there is no single framework available at the local level that might be considered or applied to secure infrastructure from private developers.The study then provides the parameters for securing contributions towards infrastructure provision. To achieve a complete understanding of this issue, it is necessary to appreciate the broader picture of what is required in terms of infrastructure for the operation of the urban environment.